Pengaruh Motivasi dan Disiplin terhadap Kinerja Pegawai PT Perkebunan Nusantara II Kebun Patumbak - Dirgantara, Rizky Nascha; Aminuddin, Aminuddin; Nasution, Ismail (Universitas Islam Islam Sumatera Utara, 2024)
This study applies quantitative methods with the aim of determining whether motivation and discipline influence on employee performance at PT. Perkebunan Nusantara II, Patumbak plantation. The population involved in this study was 34 employees and the entire population was used as a research sample. Data collection techniques were carried out by giving questionnaires to respondents, interviews, and collecting documents. To prove and analyze this, this study used several testing techniques, including validity and reliability tests, classical assumption tests, multiple linear regression tests, heteroscedasticity tests, multicollinearity tests, and f tests (simultaneous) and t tests (partial) and determination correlation tests. The results of the study showed that partially both motivation variables and discipline variables had a positive and significant effect on performance variables and simultaneously showed that employee performance at PT. Perkebunan Nusantara II, Partumbak plantation was influenced by motivation and discipline by 50.2%